Faktor Determinan Return on Asset pada Perusahaan Otomotif Yang Terdaftar di Bursa Efek Indonesia - Pulungan, Khairul Anwar; Irsan, Muhammad; Farisi, Salman (Politeknik Ganesha Medan, 2024)
Financial performance serves as information for investors and policymakers who support the implementation of company operations. Financial performance can be measured using financial ratios. This research aims to (1) find out and analyse the effect of the Current Ratio on Return on Asset, (2) know and analyse the effect of Debt to Assets Ratio on Return on Asset, (3) determine and analyse the effect of Total Asset Turnover on Return on Asset. This study uses a sample of automotive sub-sector companies listed on the IDX during the period 2016-2022. There are 12 state-owned companies listed on the IDX. A total of 9 automotive subsector companies were used as samples in this study. The sampling technique used in this research is purposive sampling. Data collection techniques use documentation techniques with secondary data. Data analysis technique The results showed that the Current Ratio (CR) variable partially did not have a significant effect on Return on Assets (ROA). The current Ratio (CR) variable partially has no significant effect on Return on Asset (ROA). The debt to asset ratio (DAR) variable is partially variable and has a negative and significant effect on return on asset (ROA). Variable Total Asset Turnover (TATO) partially has a positive and significant effect on Return on Asset (ROA). Based on the F test, the obtained variable Current Ratio (CR), Debt to Asset Ratio (DAR), and Total Asset Turnover (TATO) variables simultaneously have a significant effect on Return on Asset (ROA) have a significant effect on Return on Asset (ROA).